Otolith-based age and growth of the spotted moray eel (Gymnothorax moringa) and squirrelfish (Holocentrus adscensionis) from Ascension Island and St Helena - Valerio Visconti; Elizabeth D. L. Trip; Ian Woodgate; Tiffany Simpson; James B. Bell; Paul Whomersley; Leeann Henry; Kirsty Jones; Kyne Krusic-Golub; Simon Robertson; Serena Wright (Frontiers in Marine Science, 2025)
This study investigates the age-based life-history traits of two groundfish species, the spotted moray eel ( Gymnothorax moringa ) and squirrelfish ( Holocentrus adscensionis ), found in Ascension Island and St Helena. Both islands are part of the UK Overseas Territories (UKOTs) and are known for their fish biodiversity. The research aims to provide essential life-history information to support sustainable management of these species within the Marine Protected Areas (MPAs) of Ascension Island and St Helena. A total of 556 fish samples were collected between 2014 and 2021, with 279 individuals of G. moringa and 277 individuals of H. adscensionis . We found significant differences in life span, adult body size, and growth rates between the two islands for both species. G. moringa exhibited longer life spans (32 vs 29 years) and faster growth rates at Ascension Island compared to St Helena, while H. adscensionis showed larger adult sizes at Ascension Island but shorter life spans (21 vs 27 years) compared to St Helena. The study highlights the importance of developing locality-specific species life history data collections to monitor population dynamics in MPA areas. This biological information is essential to allow future assessment programs on the potential impacts of climate change and inshore human activities, including the impacts of inshore fisheries. Future research should focus on reproductive biology, size and age at maturity, and migration patterns to enhance the accuracy of sustainability assessments for these fisheries.

Calibration of WinSLAMM to stormwater volume and pollutant mass flux data in Ohio, USA: Informing pollutant loads in untreated stormwater from various urban land uses - Ian M. Simpson; Ryan J. Winston; Jay D. Dorsey (Journal of Hydrology, 2025)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

The role of dissolved organic carbon in Great Smoky Mountains National Park streams impacted by long-term acid deposition - Jason R. Brown; John S. Schwartz; Michael E. Essington; Qiang He; Matt A. Kulp; Ian M. Simpson (Environmental Monitoring and Assessment, 2024)

North Atlantic atmospheric circulation indices: Links with summer and winter temperature and precipitation in north‐west Europe, including persistence and variability - Ian Simpson; Edward Hanna; Laura Baker; Yiming Sun; Hua‐Liang Wei (International Journal of Climatology, 2024)
Variability in seasonal weather in north‐west Europe is substantially determined by jet stream variability. The North Atlantic Oscillation (NAO) has been well studied as a key representation of this jet stream variability, but other circulation indices are also important. Here the first three principal component empirical orthogonal functions (EOFs) of 500 hPa geopotential height (GPH), which broadly correspond to the NAO, the East Atlantic pattern (EA) and Scandinavian pattern (SCA), as well as jet speed and latitude, are correlated with temperature and precipitation anomalies over Europe with a focus on north‐west Europe, as well as measures of persistence and variability. In high summer (July and August), all three of the principal EOFs are significantly correlated with extreme temperatures in large areas of northern Europe. In winter, for much of north‐west Europe, both temperatures and precipitation are positively correlated with the jet speed, and precipitation is negatively correlated with EOF3. There is some non‐stationarity in some of the relationships, notably between winter precipitation and EOF1, and between July/August precipitation and EOF2. In addition to single variate correlations, multiple correlation coefficients are also used to determine areas of significant correlation when combining two or three of the circulation indices. The multiple correlation analyses show that combining the three EOFs produces significant correlations with temperature and precipitation over much of Europe. These analyses provide scope for using seasonal forecasts to predict likely temperature and precipitation anomalies based on predicting the atmospheric circulation anomalies and downscaling them. Improved seasonal forecasts of temperature and precipitation, including persistence and variability, will be useful to a number of users, such as agrifood, transport, energy supply and insurance.

The influence of food sensory properties on eating behaviours in children with Down syndrome - Carolyn F. Ross; C.B. Bernhard; Victoria Surette; Anne Hasted; Ian Wakeling; Sarah Smith-Simpson (Food Research International, 2024)

Magnetite trace element characteristics and their use as a proximity indicator to the Avoca Tank Cu-Au prospect, Girilambone copper province, New South Wales, Australia - Brenainn Simpson; Joel Fitzherbert; Jake Moltzen; Ian Baillie; Brad Cox; Huiqing Huang (Mineralium Deposita, 2024)
The Avoca Tank orebody is one of a series of copper-rich orebodies occurring within the Girilambone Cu province of central New South Wales. Mineralisation at Avoca Tank is hosted within several narrow, chloritic, greenschist-facies shear zones which developed ~430 Ma (U-Pb titanite) within metasedimentary rocks around the margins of an Ordovician (ca. 470 Ma) mafic sill complex. Mineralisation at Avoca Tank preserves an early oxide phase (sulfide barren) as magnetite-rich shears that are overprinted by a pyrite-chalcopyrite-rich sulfide phase. The mineralogical and chemical footprint surrounding sulfide mineralisation is narrow (<50 m) offering limited ore vectoring using mineralogical and chemical change. However, magnetite-rich shears occur external to and within sulfide mineralised intervals, and magnetite within these shears displays distinctive trace element variation depending on proximity to Cu mineralisation. Changing magnetite trace element chemistry with increasing Cu abundance at Avoca Tank is best represented by two ternary systems. A ternary plot of Ni-V-Ti effectively separates magnetite from unmineralised zones via Ni abundance, while the ratio of Ti to V effectively separates magnetite from low-, moderate- and high-grade Cu zones. A ternary plot of Sn (100*Sn)-Zn-Ni effectively discriminates between unmineralised, low-grade and combined moderate- to high-grade zones. The greatest control here is the ratio of Zn to Sn, but the inclusion of Ni abundance provides a greater separation between low- versus combined high- and moderate-grade ore. Many of the trace element trends recorded in magnetite are mirrored in the overprinting sulfides. We propose a two-phase mineralising system, with initial development of chemically uniform, sulfide barren magnetite-chlorite-rich shear zones in proximity to the margins of older mafic sills. A subsequent, and potentially hotter (+60 °C), fluid harvested the early oxide for Fe, with the partial replacement, recrystallisation and re-equilibration magnetite within a sulfide-rich hydrothermal fluid under greenschist facies metamorphic conditions. As many known orebodies in the Girilambone Cu province are associated with magnetite-rich gangue, magnetic surveys are an effective exploration technique. Based on this pilot study, mapping trace element variation in magnetite within these bodies is an additional ore-vectoring technique in the search for economic Cu mineralisation in this province.

Integrated Exposure–Response of Dupilumab in Children, Adolescents, and Adults With Atopic Dermatitis Using Categorical and Continuous Efficacy Assessments: A Population Analysis - Emily Briggs; Mohamed A. Kamal; Matthew P. Kosloski; Ian Linsmeier; Natalie Jusko; Nancy Dolphin; Jason Chittenden; Eric L. Simpson; Amy S. Paller; Elaine C. Siegfried; Brad Shumel; Noah A. Levit; et al. (Pharmaceutical Research, 2023)
Background While the majority of patients with atopic dermatitis (AD) achieve disease control with dupilumab treatment, there is variability in which patients achieve clear disease. The predictors of these responses are currently unclear. Integrated models were developed to evaluate the exposure–response (E-R) relationship of dupilumab in children, adolescents, and adults with AD. Methods Data from six Phase II and III clinical studies were pooled (2,366 adults [> 18 years], 243 adolescents [≥ 12 to < 18 years] and 359 children [≥ 6 to < 12 years]) for model development. Efficacy was assessed using the Eczema Area and Severity Index (EASI) and Investigator’s Global Assessment (IGA). Indirect response models were applied to link measures of efficacy and functional serum dupilumab concentrations. The covariates on individual placebo-corrected response were assessed. Clinical trial scenarios were simulated to compare E-R relationships across age groups. Safety was not explored. Results After correcting for differences in placebo response and dupilumab exposure: 1) older age, higher body weight, lower baseline thymus and activation-regulated chemokine, and Asian race were associated with slightly lower EASI response, and no clear covariates were identified on IGA response; 2) clinical trial simulations generally showed slightly higher response at a given dupilumab concentration in children compared to adults and adolescents with severe and moderate AD. Conclusions The collectively tested covariates explain some of the variability in dupilumab response in patients with AD. Patients in all age groups showed adequate response to dupilumab; however, children showed slightly higher drug effects compared to adults and adolescents at equivalent concentrations.

Environmental regulations in the United States lead to improvements in untreated stormwater quality over four decades - Ian M. Simpson; John S. Schwartz; Jon M. Hathaway; Ryan J. Winston (Water Research, 2023)

Hydrologic responses of single land use urban and forested watersheds and their implications to improving urban drainage design - Ian M. Simpson; Ryan J. Winston; R. Andrew Tirpak; Jay D. Dorsey; James H. Stagge; Jon M. Hathaway (Journal of Hydrology, 2023)

Monitoring the effects of urban and forested land uses on runoff quality: Implications for improved stormwater management - Ian M. Simpson; Ryan J. Winston; Jay D. Dorsey (Science of The Total Environment, 2023)

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

Webinar and survey on quality management principles within the Australian and New Zealand ACPSEM Workforce - Emily Simpson-Page; Paul Coogan; Tomas Kron; Nicholas Lowther; Rebecca Murray; Christopher Noble; Ian Smith; Rachael Wilks; Scott B. Crowe (Physical and Engineering Sciences in Medicine, 2022)

Historical overview and new directions in bioarchaeological trace element analysis: a review - Rachel Simpson; David M. L. Cooper; Treena Swanston; Ian Coulthard; Tamara L. Varney (Archaeological and Anthropological Sciences, 2021)
Given their strong affinity for the skeleton, trace elements are often stored in bones and teeth long term. Diet, geography, health, disease, social status, activity, and occupation are some factors which may cause differential exposure to, and uptake of, trace elements, theoretically introducing variability in their concentrations and/or ratios in the skeleton. Trace element analysis of bioarchaeological remains has the potential, therefore, to provide rich insights into past human lifeways. This review provides a historical overview of bioarchaeological trace element analysis and comments on the current state of the discipline by highlighting approaches with growing momentum. Popularity for the discipline surged following preliminary studies in the 1960s to 1970s that demonstrated the utility of strontium (Sr) as a dietary indicator. During the 1980s, Sr/Ca ratio and multi-element studies were commonplace in bioarchaeology, linking trace elements with dietary phenomena. Interest in using trace elements for bioarchaeological inferences waned following a period of critiques in the late 1980s to 1990s that argued the discipline failed to account for diagenesis, simplified complex element uptake and regulation processes, and used several unsuitable elements for palaeodietary reconstruction (e.g. those under homeostatic regulation, those without a strong affinity for the skeleton). In the twenty-first century, trace element analyses have been primarily restricted to Sr and lead (Pb) isotope analysis and the study of toxic trace elements, though small pockets of bioarchaeology have continued to analyse multiple elements. Techniques such as micro-sampling, element mapping, and non-traditional stable isotope analysis have provided novel insights which hold the promise of helping to overcome limitations faced by the discipline.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

MicroRNA-34a Acutely Regulates Synaptic Efficacy in the Adult Dentate Gyrus In Vivo - Birgitte Berentsen; Sudarshan Patil; Kine Rønnestad; Kevin M. Goff; Maciej Pajak; T. Ian Simpson; Karin Wibrand; Clive R. Bramham (Molecular Neurobiology, 2020)

Structural and sampling uncertainty in observed UK daily precipitation extremes derived from an intercomparison of gridded data sets - Ian R. Simpson; Mark P. McCarthy (International Journal of Climatology, 2019)
This paper compares multiple gridded data sets of daily UK precipitation to evaluate structural uncertainty in our reconstructions of historical rainfall. The data sets compared reflect two different sampling strategies and three different grid interpolation methods. In order to separate the influence of sampling and interpolation uncertainties, one of the data sets (produced by the Met Office) has been recreated using the sampling strategy of stations used in the European (E‐OBS) data set. The results confirm and build upon previous studies showing that relying on a relatively sparse but homogeneous network of stations limits the ability of the resulting data set to reliably estimate extreme rainfall at the daily timescale. It is shown that gridding methods that additionally make use of reference climatological data can avoid systematic bias in both the average and extreme events even when using a relatively sparse network of observations. This is an encouraging result in terms of our potential to reliably extend such data sets further back in time where the availability of digitized data is substantially lower than the more modern era.

Iowa Stream Nitrate, Discharge and Precipitation: 30-Year Perspective - Christopher S. Jones; Keith E. Schilling; Ian M. Simpson; Calvin F. Wolter (Environmental Management, 2018)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Analysis of compound heterozygotes reveals that the mouse floxed Pax6 tm1Ued allele produces abnormal eye phenotypes - Natalie J. Dorà; Aaron J. F. Crookshanks; Karen K. Y. Leung; T. Ian Simpson; John O. Mason; David J. Price; John D. West (Transgenic Research, 2016)

Cristobalite in the 2011–2012 Cordón Caulle eruption (Chile) - C. Ian Schipper; Jonathan M. Castro; Hugh Tuffen; Fabian B. Wadsworth; Debra Chappell; Andres E. Pantoja; Mark P. Simpson; Eric C. Le Ru (Bulletin of Volcanology, 2015)

Separate and combined effects of 21-day bed rest and hypoxic confinement on body composition - Tadej Debevec; Tarsi C. Bali; Elizabeth J. Simpson; Ian A. Macdonald; Ola Eiken; Igor B. Mekjavic (European Journal of Applied Physiology, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Lasting neurobehavioral abnormalities in rats after neonatal activation of serotonin 1A and 1B receptors: possible mechanisms for serotonin dysfunction in autistic spectrum disorders - Nidhi Khatri; Kimberly L. Simpson; Rick C. S. Lin; Ian A. Paul (Psychopharmacology, 2014)

Erratum to: Direct measurement of roots in soil for single and mixed species using a quantitative DNA-based method - Rebecca E. Haling; Richard J. Simpson; Alan C. McKay; Diana Hartley; Hans Lambers; Kathy Ophel-Keller; Sue Wiebkin; Herdina; Ian T. Riley; Alan E. Richardson (Plant and Soil, 2013)

Direct measurement of roots in soil for single and mixed species using a quantitative DNA-based method - Rebecca E. Haling; Richard J. Simpson; Alan C. McKay; Diana Hartley; Hans Lambers; Kathy Ophel-Keller; Sue Wiebkin; Herdina; Ian T. Riley; Alan E. Richardson (Plant and Soil, 2011)

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

A comparative transcript map and candidates for mutant phenotypes in the Tyrp1 (brown) deletion complex homologous to human 9p21-23 - Eleanor H. Simpson; Ruth Suffolk; Julia A. Bell; Siobhán A. Jordan; Dabney K. Johnson; Pat R. Hunsicker; Jack S. Weber; Monica J. Justice; Ian J. Jackson (Mammalian Genome, 2000)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Ecological-economic modelling of the conservation of threatened habitats: heather moorland in the Northern Isles of Scotland - Nick Hanley; Hilary Kirkpatrick; Ian Simpson; David Oglethorpe; Angus Macdonald (Biodiversity and Conservation, 1996)

Chloropropionic acid-induced alterations in glucose metabolic status: possible relevance to cerebellar granule cell necrosis - Edward A. Lock; Andrew Gyte; Peter Widdowson; Michael Simpson; Ian Wyatt (Archives of Toxicology, 1995)